Implementasi Hidden Curriculum dalam Membentuk Karakter Religius Peserta Didik di Sekolah Dasar Negeri 05 Air Tawar Barat - Melvi Melvi; Wirdati Wirdati (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
Education aims to shape the character of students to become individuals who have noble character of students to become individuals who have noble character, are independent and level others. But in fact the character crisis that occurs in society is increasingly complex. One solution solve this problem is to implement a hidden curriculum to shape religious character in schools. This research method is a qualitative method with type of case study research. The location of the research was at SDN 05 Air Tawar Barat. Daya collection methods used are observation and interview guidelines and documentation. Data analysis techniques using data reduction, data singing and drawing conclusion. The source of data from this research are the principal, vice principal, class teacher, PAI teacher. The purpose of this study was to explorr the methods used by schools in implementing the hidden curriculum. In this study, it was found that the principal and his staff used the methods of motivation, example and habituation which were carried out in the form of shool programs or routine activities carried out by the school. While the evaluation of this activity uses three indicators namely, effectiveness, adequacyadequacy and responsiveness. The results showes that activities held in schools such as morning apples, reading juz 30, asmaul husna and talqin reading Al-Fatihah and habituation of disciplined, honest, clean and responsible life were able to provide a change in attitude to students both spiritually and specially